The effect of Lectora inspire-based interactive learning media in vocational high school - Nur Rahmi Akbarini; Wiedy Murtini; Andre N Rahmanto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
The objective of research was to reveal: (1) the learning outcome of students in experiment class, (2) the learning outcome of students in control class, (3) the effect of lectora inspire-based interactive learning media on the learning outcome of students. This study was a quasi-experiment research with Pretest-Posttest Control Design with students of SMK Negeri 6 Surakarta being the subject of research. The instruments used in this research were questionnaire and test. The result of research showed that: (1) the learning outcome for experiment class indicated mean posttest value of 84.53, (2) the learning outcome for control class indicated mean posttest value of 71.73, and (3) there was an effect of Lectora Inspire-based interactive learning media on the learning outcome of students, as can be seen from the result of t-test calculation with t statistic 0,000< t table 0.05. The conclusion of research was that there was a difference of effect of lectora inspire-based interactive learning media application on the learning outcome of students between control and experiment classes.